Hereditary Multiple Gastrointestinal Atresia associated with Choledochal Cyst: A Rare Entity with Management Dilemma - P Raj; SK Sinha; S Ramji; YK Sarin (EL-Med-Pub, 2014)
Multiple intestinal atresias are rare and its treatment is challenging. Here, we present a case of multiple gastrointestinal atresia associated with choledochal cyst posing us a surgical challenge.